Identification of the drivers of and barriers to COVID-19 vaccine intake behavior using a mixed-method design: Implications from a developing country - Arash Kordestani; Pejvak Oghazi; Onur Izmir; Oguz Oypan; Serhat Ozer (Journal of Innovation & Knowledge (JIK), 2023)
Various COVID-19 vaccines are available across the world. However, short phases of clinical trials for emergency use and myriad rumors about and misinformation on vaccines spread through different media sources, induce confusion and trigger vaccine hesitancy behavior. Although clinical trials demonstrated promising results in the ability of vaccines to protect, social endeavor is required for vaccines to succeed. Mitigation of the pandemic is only possible through widespread acceptance of the vaccine. Thus, identifying the factors that impact vaccine intake is crucial. This study determined factors that affect intentions toward vaccination using a mixed-method approach, in which qualitative and quantitative analyses were conducted together. Analysis of variance (ANOVA) is used in the quantitative study, and content analysis is employed in the qualitative study. The final sample of this mixed-method study consists of 568 participants for the quantitative study and 237 for the qualitative study. They were selected using an online questionnaire. Findings suggest that social, psychological, attitudinal, perceptual, and informational factors play a crucial role in shaping people's intentions toward vaccines, ultimately influencing their decision to accept or reject vaccination. Results of both the qualitative and quantitative studies, in parallel with each other, indicated similar barriers against and drivers toward vaccine intake behavior, providing strong insights into the reasons behind vaccine acceptance and hesitancy. Based on the insights gained in this study, a set of recommendations were compiled for policymakers.
Keywords: I19; M00; 650; Covid-19 pandemic; Covid-19 vaccination; Vaccine acceptance; Vaccine hesitancy